Pharmacological Properties of NAI-603, a Well-Tolerated Semisynthetic Derivative of Ramoplanin - Jabes, Daniela (American Society for Microbiology, 2014)
NAI-603 is a ramoplanin derivative designed to overcome the tolerability issues of the parent drug as a systemic agent. NAI-603 is highly active against aerobic and anaerobic Gram-positive bacteria, with MICs ranging from 0.008 to 8 μg/ml. MICs were not significantly affected by pH (range, 6 to 8), by inoculum up to 10(8) CFU/ml, or by addition of 50% human serum. Against staphylococci and enterococci, NAI-603 was rapidly bactericidal, with minimum bactericidal concentration (MBC)/MIC ratios never exceeding 4. The frequency of spontaneous resistance was low at 2× to 4× MIC (≤1 × 10(−6) to ≤1 × 10(−8)) and below the detection limit (about ≤1 × 10(−9)) at 8× MIC. Serial subcultures at 0.5× MIC yielded at most an 8-fold increase in MICs. In a systemic infection induced by methicillin-resistant Staphylococcus aureus (MRSA), the 50% effective dose (ED(50)) of intravenous (i.v.) NAI-603 was 0.4 mg/kg, lower than that of oral (p.o.) linezolid (1.4 mg/kg) and subcutaneous (s.c.) teicoplanin (1.4 mg/kg) or vancomycin (0.6 mg/kg). In neutropenic mice infected with vancomycin-resistant enterococci (VRE), the ED(50)s for NAI-603 were 1.1 to 1.6 mg/kg i.v., compared to 0.5 mg/kg i.v. of ramoplanin. The bactericidal activity was confirmed in vivo in the rat granuloma pouch model induced by MRSA, where NAI-603, at 40 mg/kg i.v., induced about a 2- to 3-log(10)-reduction in viable bacteria in the exudates, which persisted for more than 72 h. The pharmacokinetic (PK) profiles of NAI-603 and ramoplanin at 20 mg/kg show similar half-lives (3.27 and 3.80 h, respectively) with the maximum concentration (C(max)) markedly higher for NAI-603 (207 μg/ml versus 79 μg/ml). The favorable pharmacological profile of NAI-603, coupled with the absence of local tolerability issues, supports further investigation.